Ethnobotanical survey of wild food plants traditionally collected and consumed in the Middle Agri Valley (Basilicata region, southern Italy) - Sabrina Sansanelli (Journal of Ethnobiology and Ethnomedicine, 2017)
Abstract Background This research was carried out in a scarcely populated area of the Middle Agri Valley (Basilicata region, southern Italy). The aim of the study was to record local knowledge on the traditional uses of wild food plants, as well as to collect information regarding the practices (gathering, processing and cooking) and the medicinal uses related to these plants. Methods Fifty-eight people still possessing traditional local knowledge (TLK), 74% women and 26% men, were interviewed between May–August 2012 and January 2013, using open and semi-structured ethnobotanical interviews. For each described plant species, the botanical family, the Italian common and folk names, the plant parts used, the culinary preparation and, when present, the medicinal use, were recorded and the relative frequency of citation index (RFC) was determined. Results The 52 plant species mentioned by the respondents belong to 23 botanical families, with Asteraceae (12 plants) and Rosaceae (7 plants) being most frequently cited. The species with the highest RFC index is Cichorium intybus L. (0.95), followed by Sonchus spp. (S. oleraceus L., S. asper L. and S. arvensis L.) (0.76). The plant parts preferably used are leaves (22 plants), fruits (12) and stems (7). Only six wild plants were indicated as having both food use and therapeutic effect. Conclusions The survey conducted on the traditional use of wild food plants in the Middle Agri Valley revealed that this cultural heritage is only partially retained by the population. Over the last few decades, this knowledge has been in fact quickly disappearing along with the people and, even in the rural context of the study area, is less and less handed down to younger generations. Nevertheless, data also revealed that the use of wild plants is recently being revaluated in a way closely related to local habits and traditions.